Alchemy : the art and craft of illustration - Wang, Shaoqiang (Sandu Publishing Co., Ltd, 2016)
"No longer confined to a flat medium, illustration has been liberated to new heights of fancy limited solely by the imaginations of today's leading artists. Some employ paper cutting to create multilayered worlds that you look into rather than upon. Others work with fabric or thread, embroidering colorful conceptual masterpieces that have the ability to shock or surprise. Still others make use of mixed media, not wishing to be limited by choice of material when crafting their individual visions. Whether two or three dimensional, each of the artworks featured reflect an entirely unique voice, which expands upon the very definition of illustration. Artists include Gregory Euclide, Frank Plant, Chris Maynard, Christine Kim, Bovey Lee, and Irma Gruenholz"--Publisher's description.